6k-3-2k=k-22

Simple and best practice solution for 6k-3-2k=k-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k-3-2k=k-22 equation:


Simplifying
6k + -3 + -2k = k + -22

Reorder the terms:
-3 + 6k + -2k = k + -22

Combine like terms: 6k + -2k = 4k
-3 + 4k = k + -22

Reorder the terms:
-3 + 4k = -22 + k

Solving
-3 + 4k = -22 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-3 + 4k + -1k = -22 + k + -1k

Combine like terms: 4k + -1k = 3k
-3 + 3k = -22 + k + -1k

Combine like terms: k + -1k = 0
-3 + 3k = -22 + 0
-3 + 3k = -22

Add '3' to each side of the equation.
-3 + 3 + 3k = -22 + 3

Combine like terms: -3 + 3 = 0
0 + 3k = -22 + 3
3k = -22 + 3

Combine like terms: -22 + 3 = -19
3k = -19

Divide each side by '3'.
k = -6.333333333

Simplifying
k = -6.333333333

See similar equations:

| x*x-14x+33=0 | | -5=-2-3 | | -6z=3x | | x=-7+7 | | 7-8x=87-43x | | 2x-8y=-11 | | 30x*-6= | | 20x-45= | | -7x+5=48+x+45 | | y=-2(-7+y)+7 | | 2x-y+2z=-8 | | 2x^2+x-3=18 | | 4(7x-1)=5(2x+1) | | (2x-17)+1x+59=360 | | 4x+20=45-x | | x=18+-7(2) | | 2x-2=-8+3x | | 5(y-3)-3(y-2)=8 | | (3)/(8)x-(1)/(4)=2 | | 40-x=12x | | 48=4n/7+n | | -8(-3)(-3)= | | y=-4(18+-7y)+18 | | 4z-11-z+2=0 | | -2x(5x-8)=6x | | 8a+3=3 | | 9x-1=125 | | 1/8(5x+4)=3.4 | | (1)/(8)x=(1)/(2) | | (x-5)/(3*x)+(6/2*x+1)=0 | | (8x+9)(7x^2+9x+9)= | | (5)/(6)x=-15 |

Equations solver categories